2017
DOI: 10.3389/fpls.2017.00857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Quality on Morphology, Enzyme Activities, and Bioactive Compound Contents in Anoectochilus roxburghii

Abstract: The aim of this study was to investigate the effects of light quality on the morphological traits, leaf anatomical characteristics, antioxidant enzyme (superoxide dismutase, catalase, and peroxidase) activities, photosynthetic pigments content, and bioactive compounds (phenols, flavonoids, and polysaccharides) content in Anoectochilus roxburghii. Plants of A. roxburghii were grown under light filtered through four differently colored films for 8 months. The four treatments were red film (RF), blue film (BF), y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 26 publications
5
46
4
Order By: Relevance
“…The total Chl content decreased under monochromatic light, indicating that monochromatic light causes damage to the photosynthetic pigments. However, compared to R light, B light treatment resulted in significantly higher leaf Chl content, which is inconsistent with the results of studies on lettuce and Anoectochilus roxburghii [46,47]. In this study, the P n of Welsh onion seedlings was significantly lower when grown under monochromatic light than under the W light treatment, especially under Y and G lights (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…The total Chl content decreased under monochromatic light, indicating that monochromatic light causes damage to the photosynthetic pigments. However, compared to R light, B light treatment resulted in significantly higher leaf Chl content, which is inconsistent with the results of studies on lettuce and Anoectochilus roxburghii [46,47]. In this study, the P n of Welsh onion seedlings was significantly lower when grown under monochromatic light than under the W light treatment, especially under Y and G lights (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Nowadays, some spectrum LEDs or films have been used in indoor plant pre-cultivation (or in greenhouse) at seedling developmental stage to promote the growth traits and the accumulation of bioactive compounds in economic or medicinal trees, such as Quercus ithaburensis and Anoectochilus roxburghii ( Smirnakou et al, 2017 ; Ye et al, 2017 ). Previous studies have reported the effects of differential light quality and light intensity on the development of C. paliurus , such as biomass and polysaccharide accumulation ( Yang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that plants would adapt to the environmental condition both physiology and morphology (Gong et al 2018) and it is recorded that plasticity of plant has been recorded as a good way of plant in responding the different environmental conditions (Frei et al 2014). In addition, the plant plasticity of stem will be influenced by light intensity (Ye at al. 2017).…”
Section: Discussionmentioning
confidence: 99%